Leisure and aging theory and practice - Gibson, Heather J. (Heather Julie); Singleton, Jerome F. 1950- (Champaign, IL Human Kinetics, 2012)
The number and percent of older people in developed countries continue to grow, thanks to medical advances and decreases in fertility and mortality rates. And that means that tomorrow's recreation and leisure professionals will be more challenged than ever to meet the needs of an increasingly older culturally diverse population. Leisure and Aging: Theory and Practice provides students and professionals with a balanced perspective of current knowledge as it presents cutting-edge research from the fields of both gerontology and leisure studies. Written by authors from various disciplines who represent an international who's-who in leisure and aging research, this text: explores theories in leisure and aging; bridges the gap between research and application, arming professionals with tools to navigate diverse cultures; and offers insight into delivery of leisure services in older adult communities and long-term care environments. Each chapter features learning objectives, study questions, case studies, exercises, and relevant readings. The book is supplemented by online ancillaries, including an instructor guide, test package, and a presentation package with photos, illustrations, and tables from the text. Together, the text and online ancillaries help students connect theories and practice as they prepare for future roles in their chosen fields. Leisure and Aging is presented in five sections. Part I introduces global perspectives on leisure and aging, while part II examines the relevance of leisure in an aging context. Part III explores the effects of aging on physical, psychological, social, and spiritual well-being and health. Parts IV and V delve into the role of community in aging and leisure and long-term care and leisure. Written for undergraduate students, professors, and professionals in recreation, leisure, gerontology, and aging, Leisure and Aging provides a wealth of knowledge on various aspects of life for older people and the role of leisure in their lives. The text helps students think critically about a phase of life that seems remote from their own and provides perspective to their understanding of aging and leisure.
Part I. Setting the Stage -- Chapter 1. Global Perspectives on Leisure and Aging / Richard D. MacNeil and David L. Gould ; Demography and Population Aging ; Global Aging: Current and Future Status ; Leisure and Quality of Life in Older Adulthood ; Conclusion ; Learning Aids -- Chapter 2. The Influence of Leisure on Discourses of Aging / Rylee A. Dionigi and Sean Horton ; Negative Aging Discourse ; Positive Aging Discourse ; Leisure as Resistance to Ageism ; Leisure as Reinforcement of Ageism ; Conclusion ; Learning Aids -- Part II. Theoretical and Methodological Perspectives on Leisure and Aging -- Chapter 3. The Relevance of Leisure in Theories of Aging / Douglas A. Kleiber and M. Rebecca Genoe ; Leisure as a Context for Continuity and Change ; Psychological Theories of Aging ; Sociological Theories of Aging ; Conclusion ; Learning Aids -- Chapter 4. Studying Leisure in the Context of Aging / Bryan Smale and Jennifer Gillies ; Epistemological Perspectives Guiding Research ; The Role of Theory ; Two Broadly Defined Approaches to Research ; Quantitative Inquiry ; Qualitative Inquiry ; Roles and Responsibilities of the Researcher ; Doing Research Well ; Conclusion ; Learning Aids -- Chapter 5. Leisure Across the Later Life Span / Galit Nimrod and Megan C. Janke ; Life-Span Development Models ; Changes in Leisure Behavior as People Age ; Changes in Leisure Meanings as People Age ; Leisure and Later-Life Transitions ; Time Misuse in Later Life ; Conclusion ; Learning Aids -- Chapter 6. Leisure and Diversity in Later Life: Ethnicity, Gender, and Sexual Orientation / Steven E. Mock, Susan M. Shaw, Erica M. Hummel, and Carissa Bakker ; Critical Gerontology ; Ethnicity and Race ; Gender ; Sexual Orientation ; Conclusion ; Learning Aids -- Part III. Leisure and Healthy Aging -- Chapter 7. Leisure and Physical Well-Being / Bevan C. Grant and Mary Ann Kluge ; Health Maintenance as a Benefit of Physical Leisure ; Constraints to Engaging in Physical Leisure ; Implications for Programming ; Integrating Leisure and Physical Activity ; Accessing the Meaning of Active Aging ; An Active Future ; Conclusion ; Learning Aids -- Chapter 8. Leisure and the Psychological Well-Being and Health of Older Adults / Roger C. Mannell and Ryan Snelgrove ; Leisure and Psychosocial Well-Being ; Leisure and the Cognitive Health of Older Adults ; Conclusion ; Learning Aids -- Chapter 9. Leisure and Social and Spiritual Well-Being / Paul Heintzman and Erin Patriquin ; Defining Key Concepts ; Aging, Leisure, and Social Well-Being ; Aging, Leisure, and Spiritual Well-Being ; Leisure-Spiritual Coping Model ; Conclusion ; Learning Aids -- Part IV. Community, Aging, and Leisure -- Chapter 10. The Role of Community in Encouraging Healthy Aging Among Older Adults / Richard Gitelson and Julie Freelove-Charton ; Impact of Choice and Environment on Health ; Active Adult Communities ; Resources in Communities Without Age Restrictions ; Conclusion ; Learning Aids -- Chapter 11. Tourism and Aging / Ian Patterson and Shane Pegg ; Sociodemographics of Travel ; Meanings of Tourism ; Motivations to Travel ; Constraints to Travel ; Modes of Travel ; Temporary Communities ; Older Mobile Travelers ; Research on Snowbirds ; Adventure Tourism ; Educational Tourism ; Conclusion ; Learning Aids -- Part V. Leisure in Long-Term Care -- Chapter 12. Leisure in Long-Term Care Settings / Sherry L. Dupuis, Colleen Whyte, and Jennifer Carson ; Predominant Culture Within Long-Term Care Settings ; Alternative Approaches to Care in Long-Term Care Settings ; Quality of Life Through Leisure in Long-Term Care Settings ; Reflection and Practice ; Conclusion ; Learning Aids -- Chapter 13. Bridging Community and Long-Term Care Settings / Elaine Wiersma and Stephanie Chesser ; Definition of Concepts ; Transition From Community Settings to Long-Term Care Settings ; Concepts of Community in Long-Term Care Settings ; Creating Community in Practice ; Conclusion ; Learning Aids.
Includes bibliographical references
Keywords: Aging; Leisure -- Social aspects; Older people -- Recreation